Political Status of Zakho District (Hassania) And Its Adjacent Citadels During the Ilkhani and Jalayeri Mogul States (6656 – 823 H./ 1258-1420 AD.) - Sheikh Mohammed, Rabeah F. (Humanities Journal of University of Zakho, 2017)
Zakho district (Hassania) and its adjacent citadels during the IlKhani and Jalayeri Mogul states (6656 – 823 H./ 1258-1420 AD.) were linked administratively to Amadiya , which was the nearest political entity in the area. Amadiya itself belonged to Hakari as well. A great number of big clans such as Sindi, Mehrani, Sinni, Rehzadi, and other tribes were dwelling there. There were also many independent citadels and forts there such as Hassania, Shabani, Zafaran, Bajilaya, Eramdesht, Kuashi, Shiransh, Rabia, Elqi, Fereh, Sirwa, Jerrahia, and many other small fortresses in the area. During the Mogul attack and the fall of Baghdad (656 H/1258 AD.), the Zakho citadels and forts did not face the Mogul attacks because they were under the rule of the Attabecks of Mosul. As such, it is seen that Bedreddin Lu’lu’I, the ruler of Mosul has expressed his loyalty to the Moguls, Izzaddin Eibeck, the ruler of Amadiya and the representative of Lu’lu’I, followed suit and expressed his loyalty as well, and the citadel of Zakho district were under his control. Though the princes and tribal heads, especially the Mehrani ones, turned towards the Ayubbid State, other tribes such as the Sindi tribe that had many fighters could fill their place. By the end of the IlKhani Mogul state there appeared an independent area in Amadiya on one hand. On the other hand, the independent citadels and forts in Zakho area and weakening the role of the central state during the Jalayeri state helped Zakho district to have its independent army and fighters related directed to the citadels and the tribes there; they were under the direct order of the princes of these citadels and forts.